Both Questionable and Open Research Practices Are Prevalent in Education Research. (November 2021) - Makel, Matthew C.; Hodges, Jaret; Cook, Bryan G.; Plucker, Jonathan A.
Concerns about the conduct of research are pervasive in many fields, including education. In this preregistered study, we replicated and extended previous studies from other fields by asking education researchers about 10 questionable research practices and five open research practices. We asked them to estimate the prevalence of the practices in the field, to self-report their own use of such practices, and to estimate the appropriateness of these behaviors in education research. We made predictions under four umbrella categories: comparison to psychology, geographic location, career stage, and quantitative orientation. Broadly, our results suggest that both questionable and open research practices are used by many education researchers. This baseline information will be useful as education researchers seek to understand existing social norms and grapple with whether and how to improve research practices.